Global Strategies for Disease Detection and Treatment : Proteomics. - Hanash, S. (IOS Press, 2002)
The field of proteomics holds great promise for identifying non-targeted, global molecular profiles "signatures" of normal and diseased cells. This work shows that strategies based on the separate analysis of subcellular compartments provide the means to determine protein location in a cell.